Role of Wireless Body Area Networks in Intelligent Transportation Systems: A Survey - Chhabra, Rishu; Prabaharan, Beski; Aggarwal, Rashmi (International Journal of Sensors Wireless Communications and Control, 2021)
The employment of wireless body sensors for different applications like healthcare and transportation systems has been a key research area. The hybrid systems that combine the wearable wireless sensor technology for safety applications in transportation infrastructure to save the life of the drivers and Vulnerable Road Users (VRU) like cyclists and pedestrians is another step towards the aim of Intelligent Transportation Systems (ITS) to improve safety on roads. The systems in the literature involve the use of sensors fixed on or around the body of the driver and/or pedestrian, sensors embedded in smart devices like smartphone, smartwatch, and tablets, etc. to alert the drivers and pedestrians in advance to prevent the probability of collision and prevent road accidents. The sensors are able to detect the behavior of the driver and identify whether he/she is fit for driving a vehicle. The presence of a distracted pedestrian is another cause of the collision, and nearby vehicles should be informed about the same. In this paper, different systems in the literature that employ wireless body sensors to improve the safety of the commute have been reviewed. The techniques reviewed in this paper focus on the safety of the driver and VRU/pedestrian. The paper concludes by presenting key challenges and future research directions to prevent accidents by the integration of wireless body sensor networks as a part of an intelligent transportation system.
Keywords: sensor Wireless Body Area Network (WBAN)